The provision of ICU outreach and its impact on ICU survivors, families and healthcare professionals - Mohamed Ludin, Salizar (2014)
Patients who need critical care are among the sickest in a hospital and require a high level of clinical and technical expertise (Department of Health, 2005). There has been a considerable amount of evidence on the effectiveness of the care this patient group receives and much of this resulted in the assertion that critical care should be regarded as a description of a patient’s care needs rather than a place of care (DH, 2000), and a recommendation that Critical and Intensive care outreach services be developed. (Hainsworth, 2006). Research has shown that providing early intervention to patients with deteriorating conditions by critical care health care providers outside the walls of the ICU decreases the incidence death following cardiac arrest, length of hospital stay related to cardiac arrest, post-operative adverse outcomes, post-operative mortality rate, and length of hospital stay (Ball, Kirkby, & William, 2003; Bellomo et al., 2003 DeVita et al., 2004). It was shown that 30 percent the number of documented cardiac arrests after implementation of a critical care team that works outside of ICU (Canadian Healthcare Technology, 2007) decreased.